A case of intestinal failure associated with meconium peritonitis requiring transanal decompression using a Kangaroo New Enteral Feeding Tube - Mitsumasa Okamoto; Eisuke Terasaki; Mutsuko Kuribayashi; Harunori Miyauchi; Yudai Tsuruno; Hiroaki Fukuzawa; Tomoaki Ioroi; Masaaki Kugo (Elsevier, 2022)
Meconium peritonitis is a congenital disorder characterized by intestinal perforation in utero and presents as sterile chemical peritonitis. When intraabdominal chemical inflammation is severe, intestinal decompression may be required to control intestinal failure due to severe adhesions. In this case, we safely controlled intestinal failure by transanal decompression using a Kangaroo New Enteral Feeding Tube (EF tube) because oral intestinal adhesions were severe and conventional transoral decompression was not feasible. Given the risk of anastomotic leakage and the potential time needed to improve intestinal failure, transanal decompression by EF tube should be considered when transoral decompression proves difficult.